The Reality and Challenges of Teachers in Realizing Innovative Learning in Elementary Schools - Husnul Khotimah; Lisa Amilda; Sahikmah Ezi; Abdurrahmansyah Abdurrahmansyah (Peneliti.net, 2026)
Innovative learning is an important approach inimproving the quality of teaching and learning processes in elementary schools. Teachers are required to create creative, active, and student-centered learning in order to develop students’ critical thinking and 21st- century skills. However, in practice, there are still various challenges faced by teachers in implementing innovative learning in the classroom. This study aims to analyze the realities and challenges faceed by elementary school teachers in implementing innovative learning. The method used in this study is a library research findings. The results of the study show that several major challenges faced by teachers include limited pedagogical competence, inadequate learning facilities and infrastucture, high administrative workload, differences in students characteristics and abilities, and the demands of curriculum changes. Therefore, various efforts are needed, such as improving teacher compotence, providing adequate learning facilities, and strengthening educational policies to support the implementation of innovative learning effectively in elementary schools.